2021
DOI: 10.21037/jtd-21-130
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic signs of pulmonary hypertension in patients with newly recognized hypersensitivity pneumonitis, prevalence and clinical predictors

Abstract: Background: Hypersensitivity pneumonitis (HP) is the third, according to frequency, interstitial lung disease, with the estimated incidence rate of 1-2/100,000. In HP patients, the extensive inflammatory lesions encompassing both small airways and lung parenchyma, as well as subsequent development of lung fibrosis, may result in respiratory insufficiency and secondary pulmonary hypertension (PH). The aim of the present retrospective study was to assess the prevalence of echocardiographic signs of PH and its' c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
2
6
1
Order By: Relevance
“…More recent study conducted on 70 patient with HP considered PH diagnosis in 37% of patients based on echocardiography, authors noticed that patient with HP and PH has significant reduction of resting PO 2 and 6MWD and O 2 desaturation rate, this was close to our results [ 4 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…More recent study conducted on 70 patient with HP considered PH diagnosis in 37% of patients based on echocardiography, authors noticed that patient with HP and PH has significant reduction of resting PO 2 and 6MWD and O 2 desaturation rate, this was close to our results [ 4 ].…”
Section: Discussionsupporting
confidence: 91%
“…Dybowska et al found that fibrotic HP was not a predictor of PH on echocardiogrsphy when they use PASP 36 mmHg as cut off of diagnosis of PH, but PASP > 50 mmHg was exclusively observed in fibrotic HP. So, they declared that role of pulmonary fibrosis as predictor of PH in HP was not clear, which is not in line with our findings [ 4 ].…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Attention should be paid to a significant difference in the frequency of PH between medical documentation at the time of a patient’s inclusion in the study and the results obtained after the patient’s examination (TTE)—32.9% vs. 48.2%. The problem of underestimating PH in patients with HP has been confirmed by Wälscher et al, who assessed comorbidity in patients with chronic HP and showed a frequency of PH as high as 9.5% (20 out of 211 patients); this is significantly lower than the frequency of PH diagnosis based on medical records [ 8 , 10 , 15 ]. An important advantage of our study is an assessment of right heart size and function by TTE.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, PH can also be detected in patients with IPF without hypoxemia with mild to moderate impairment of lung function [ 7 ]. Data on PH prevalence among patients with HP are more limited; most authors report a frequency of 28.3–44.0% [ 8 , 9 , 10 ]. Several studies have confirmed a significant impact of PH on the risk of mortality in patients with IPF [ 7 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%